An Analysis of the Implementation of the Merdeka Curriculum in Inclusive Schools in East Lombok Regency - Karomi; Murah; Syahidallah; Junayanti, Maryana (JoIEM (Journal of Islamic Education Management), 2024)
This research aims to analyse the implementation of the Merdeka curriculum in inclusive schools in East Lombok Regency. Considering the large number of people with disabilities in this area, this research explores the challenges faced by teachers in interactions with students, understanding the curriculum, as well as available resources. Qualitative descriptive research method was used, with data obtained through observation, interviews, and documentation. The results of research on the implementation of the Merdeka curriculum in inclusive schools in East Lombok show a significant positive impact on the development of inclusive students, especially in the aspects of communication, motor, cognitive, and independent ability. This success was influenced by the teacher's understanding in implementing differentiated learning and support from special inclusion teachers. However, there are still challenges, such as limited resources and training, as well as a learning culture that is not yet inclusive. To increase the implementation of the Merdeka curriculum in inclusive schools, ongoing training, development of individual learning plans, and improvement of facilities are needed. Supports from the government, schools, and community are critical to long-term success. It is hoped that this research can contribute to the development of a sustainable and responsive inclusive education environment in East Lombok.